The effect of strategic behavior typology on organizational excellence: “A study of the opinions of the heads of scientific departments in a number of private universities in the kurdistan region of Iraq” - Omar, Zeravan; Yousif , Mehvan (Humanities Journal of University of Zakho, 2023)
Global competition, a dynamic environment, and shrinking resources have created a lot of pressure on today's institutions including private higher education institutions (HEIs). Hence, the need for efficient strategic tools and keys capable of not only ensuring efficient use of resources but, also responding to the rapid dynamism of today's environment to gain organizational excellence and to enhance the performance of higher education institutions and their importance as well. The current study examined the direct effect of strategic Behavior (SB) on organizational excellence (OE). The data was gathered from 181 heads of scientific departments from a number of private universities in the Kurdistan region, which were analyzed using the both PLS-SEM version (4.0.7), and the Spss version (26). The results of the analysis showed that strategic Behavior (SB) had significantly related to organizational excellence (OE), the results also present that strategic Behavior has a significant effect on organizational excellence except for the reactor’s Behavior pattern, which had an insignificant effect on organizational excellence. Thus, the results of the current study will give additional insights into the appropriate strategic Behavior patterns to reach organizational excellence in private universities in the Kurdistan Region.